The impact of HRM digitalization on firm performance: investigating three‐way interactions. (7th April 2020) - Zhou, Yu; Liu, Guangjian; Chang, Xiaoxi; Wang, Lijun
Abstract : In this study, drawing from adaptive structuration theory (AST) and embeddedness theory, we investigate the relationship between the interaction of HRM digitalization and HRM system maturity on firm performance as well as the moderating role played by HR strategic and business involvement. On the basis of a sample of 211 listed enterprises of China, our results indicate that the interaction of HRM digitalization and HRM system maturity is positively related to firm performance and that the relationship is strengthened by HR strategic and business involvement. The implications of our findings for research and practice are discussed. Key points: HRM digitalization can release a significant main effect to enhance firm performance. The maturity of HRM systems can strengthen the positive effect of HRM digitalization on firm performance. When HR departments are deeply involved in the organization's strategic management, the positive influence of HRM digitalization will be increased. When HR departments are deeply involved in the business operation, the positive impact of HRM digitalization will be enhanced.